Biological Flora of Britain and Ireland: Liparis loeselii: No. 304. (20th March 2023) - Jacquemyn, Hans; Pankhurst, Tim; Jones, Peter S.; Brys, Rein; Hutchings, Michael J.
Abstract: This account presents information on all aspects of the biology of Liparis loeselii (L.) Rich. (Fen Orchid) that are relevant to understanding its ecological characteristics and behaviour. The main topics are presented within the standard framework of the Biological Flora of Britain and Ireland : distribution, habitat, communities, responses to biotic factors, responses to environment, structure and physiology, phenology, floral and seed characters, herbivores and disease, and history and conservation. Liparis loeselii is a small terrestrial orchid that has a circumboreal distribution and is widespread in Europe and North America. Despite its wide distribution, the species is locally rare and has declined considerably in most of its range. In Britain, the species has a disjunct distribution and is now known to occur consistently at only six sites in eastern England and three in south Wales. It is absent from Ireland. Its most characteristic habitats in Britain are inland fens and coastal dune slacks, but outside Britain it can also be found in wet meadows, marshes, forested seep springs, at lake borders or on mats of floating peat. Populations of Liparis loeselii in dune slacks tend to be short‐lived, and can rapidly increase in size or decrease and disappear as environmental conditions change. The species does not tolerate high nutrient concentrations or low pH. It is susceptible to drought, which reduces seed germination, seedling recruitment and adult survival. Heavy predation by rabbits and rodents has been observed under drought conditions. Liparis loeselii reproduces both by sexual reproduction, and by vegetative propagation through the production of pseudobulbs. Although flowers are accessible to insects, entomophilous pollination is unusual, and most sexual reproduction is the result of selfing. Fruits ripen late in the growing season (mid‐October) and the dust‐like seeds are dispersed during winter by wind and water. Germination occurs during the following growing season and is supported by a wide variety of mycorrhizal fungi. Since the late 19th century Liparis loeselii has declined considerably in Britain and elsewhere in Europe, primarily due to habitat destruction and loss, natural succession, and habitat desiccation due to drainage. As a result, the species has been listed as endangered in the Bern Convention and the European Habitat Directive (92/43/EEC) and is the focus of intensive conservation efforts in many countries. Restoration of habitat by mowing, extensive grazing and peat removal, and the creation of new habitat by dune slack formation in dune systems and peat removal in fens may prolong population persistence and promote establishment of new populations. Abstract : In this paper, the authors provide a thorough account on all aspects of the biology of the Fen Orchid ( Liparis loeselii (L.) Rich.). This species has seen a remarkable decline throughout most of its distribution area in Europe and is currently the focus of intensive conservation efforts in many countries.